Burger terbang / Muhammad Hafizz Asyraf Hamizul, Aiman Qayyum Mohd Ali Hanifiah and Ammar Shahmy Abdul Aziz - Hamizul, Muhammad Hafizz Asyraf; Mohd Ali Hanifiah, Aiman Qayyum; Abdul Aziz, Ammar Shahmy (2021)
Burger Terbang is a company with 3 partner with clear goal to succeed in business. Burger Terbang is a food and drinks business that provides special services in serving food and drinks. Due to high potential and population of people, this business will be located at Seri Alam. Our type of business is always having high demand because our business will place at Food Village, Seri Alam which near to the school and residential area. We believed that with the high population there, Burger Terbang as business that offers food and drink services will fulfil our customer needs and wants. Marketing plan plays a huge role in achieving the goals and profitable outcome in a business. Besides that, it can help the entrepreneur to let the other people know about their product and grow their business.